ABILITY TO PAY AND WILLINGNESS TO PAY ANALYSIS OF CLEAN WATER NEEDS FROM DUSUN SEPURAN, JEMBER REGENCY - Agus Luthfi; Moh. Saleh; Maryunani Maryunani; Herman Cahyo Diartho (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2017)
This research aimed to discover how Dusun Sepuran society could fulfill clean water needs using Ability to Pay (ATP) and Willingness to Pay (WTP) approach. This research used quantitative analysis method affirmed by qualitative method. Based on data processing result, it was known that Dusun Sepuran society ATP categorized within captive rider category. It means that, ATP value for water needs proportion is lower than WTP. This is due to high Electricity Base Tariff Rate which cause water fulfillment cost, as most of Dusun Sepuran people must use water pump. Therefore proper policy implementation is necessary in handling water crisis threat at Dusun Sepuran in the future